Glicerina bruta, oriunda da produção do biodiesel, no suplemento para terminação de cordeiros lactentes em pastejo - Pellegrin, Ana Carolina Ribeiro Sanquetta de (2012)
The objective of this research was to evaluate the effect of levels of crude glycerin in replacement of corn for suckling lambs kept on pasture ryegrass (Lolium multiflorum Lam.) supplemented in creep feeding on the characteristics of the pasture, supplement intake, performance, carcass characteristics, corporal components, physico-chemical and sensorial characteristics of meat. Thirty two suckling lambs were used and were kept with the sheep until slaughter, were from single or double birth, the lambs had about 29 days old and the initial body weight of 12,32±1,59 kg. They were equally distributed by sex, type of birth and weight among the treatments: 0, 10, 20 or 30% of crude glycerin, which contained 84,8% glycerol, in the replacement of corn in the isoprotein supplement (18% CP) daily provided in amounts equivalent to 2% live weight for each animal. It was evaluated the characteristics of ryegrass pasture, the supplement intake and performance of lambs that were slaughtered when they reached pre-established slaughter weight of 28 kg of body weight, with 14 hours for fasting solid. After were evaluated carcass traits, corporal components and characteristics of lamb meat. The experimental design adopted was randomized blocks and each data of variables were subjected to analysis of variance at 5% significance level and the significant results were submitted to regression analysis. Up to 30% of crude glycerin in the supplement provided in creep feeding not influenced (P>0,05) the characteristics of ryegrass pasture, supplement intake and performance of suckling lambs kept on pasture, but changed (P<0,05 ) the carcass characteristics and corporal components. There was an increase in the weights and proportions of rumen, omasum, large intestine and skin of animals which influenced the reduction of weight and yield of hot and cold carcass and an increase in gastrointestinal contents and loss by fasting. There was effect (P<0,05) of levels of crude glycerin on the deposition of body fat, with a decrease in fat deposition in the shoulder and kidney fat. There was no depreciation (P>0,05) in the physico-chemical and sensorial characteristics of lamb meat, but the pH values and cooking losses of meat increased (P<0,05). Based on the results obtained in this research, it is concluded that the crude glycerin can be used by up to 30%, replacing the corn in the creep feeding supplementation of suckling lambs kept in ryegrass pasture with no negative effects on intake, performance and lamb meat characteristics, however, negative effects were observed in carcass quality and fat deposition in the animal body.